PENGARUH PENGGUNAAN SHOPEE PAYLATER DAN PROMO HARBOLNAS (HARI BELANJA ONLINE NASIONAL) TERHADAP IMPULSE BUYING PENGGUNA SHOPEE DI KOTA MEDAN - Panjaitan, Simon Partahi; Marpaung, Nicholas (Transpublika Publisher, 2023)
This study aims to analyze the influence of Use Of Shopee PayLater and Harbolnas promos on Shopee users in Medan. The influence between Shopee PayLater and the Harbolnas promo will be analyzed partially and simultaneously on impulse buying for Shopee Users in Medan City. The research method used in this research is quantitative research with an associative approach. Sampling was carried out using a non-probability sampling technique, and the method used was purposive sampling with 100 respondents as a sample. The data collection method used in this study was primary data obtained through questionnaires through Google form, while secondary data was obtained through library research. The analytical method used is the validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of the research conducted show that the Use Of Shopee PayLater variable (X1) and the Harbolnas promo (X2) have a partial and significant effect on Impulse Buying (Y), the Use Of Shopee PayLater variable (X1) and the Harbolnas promo (X2) also have a simultaneous and significant effect on Impulse. Buying (Y), the value of this coefficient shows the relationship between Use Of Shopee PayLater (X1) and the Harbolnas promo (X2) to Impulse Buying (Y) is very strong with an R value of 0.724 or 72.4%. It is also known that the Adjusted R Square value of Use Of Shopee PayLater (X1) and Harbolnas promos (X2) can explain the Impulse Buying variable by 51.4%. At the same time, the rest is influenced by other variables not discussed in this study.